Pengaruh Beban Kerja dan Kompensasi terhadap Kinerja Karyawan pada PT Gifera Odo Technology Jakarta Barat - Fariza Ayu Futriyani; Furi Indriyani; Rohani Lestari Napitulu (Jurnal Manajemen Bisnis Digital Terkini, 2025)
The rapid development of information technology and increasing global competition require companies to continuously improve human resource performance. One effort that can be done is by paying attention to the workload received by employees and the compensation system provided. The background of this study is based on the declining trend of employee performance in the last three years, which indicates that performance is not yet fully optimal. This study uses a descriptive quantitative approach. Data were obtained by distributing questionnaires to 50 respondents working in various divisions. The data analysis technique used multiple linear regression with the help of SPSS version 25. The results of the study indicate that workload and compensation simultaneously have a significant effect on employee performance, with a coefficient of determination (R²) of 59.5%. The results show that: 1). Workload has a negative and significant effect on Employee Performance, 2). Compensation has a positive and significant effect on Employee Performance. These findings indicate that employee performance can be improved through a balanced distribution of workload and the provision of appropriate and fair compensation. The implications of this study provide a basis for companies in developing more effective human resource management strategies oriented towards improving performance.